Venous Thromboembolism: A Survey of Oral Anticoagulant Preferences in the Treatment of Challenging Patient Populations. (December 2018) - Moyer, Genevieve Claire; Bannow, Bethany Samuelson; Thornburg, Courtney; Rosovsky, Rachel; Wang, Tzu-Fei; Woller, Scott; Thornhill, Dianne; Kreuziger, Lisa Baumann
Venous thromboembolism (VTE) is a highly morbid condition with several available oral anticoagulant treatment options. Numerous studies have been published comparing warfarin to direct oral anticoagulants; however, several populations remain underrepresented in these reports. We surveyed members of The Venous ThromboEmbolism Network U.S. working group regarding their oral anticoagulant preferences for the treatment of VTE in different and challenging populations. In individuals with VTE and no other medical comorbidities, respondents preferred either rivaroxaban (48.7%) or apixaban (48.7%). Apixaban (53.3%) was preferred in elderly individuals with an increased risk of bleeding. Warfarin was preferred in individuals with liver or kidney dysfunction (42% and 47%), altered metabolism (>55%), and antiphospholipid antibody syndrome (84.2%). Low-molecular-weight heparin was preferred in individuals with malignancy (56.6%), followed by edoxaban (23.7%). These findings may help guide clinicians when choosing an anticoagulant in these challenging situations and demonstrate the urgent need for additional study in these groups.